2006
DOI: 10.1029/2006jb004561
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature magnetic behavior of multidomain titanomagnetites: TM0, TM16, and TM35

Abstract: [1] An unpredicted effect of the Verwey transition in magnetite is that a field-cooled (FC) remanent magnetization can be less intense than a zero-field cooled (ZFC) isothermal remanence. The effect, only documented in a handful of multidomain (MD) samples, is thought to be unique to MD material. Data for new MD samples all show an elevation of ZFC over FC remanences. Current theory suggests that the FC easy axis bias alone produces the effect. We measured hysteresis loops after three cooling pretreatments; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 60 publications
(82 reference statements)
9
40
1
Order By: Relevance
“…Because in MD grains saturation remanence is related to coercivity through the demagnetizing factor (SIRM ∝ H c /N ; e.g., Dunlop andÖzdemir, 1997), ZFC SIRM will be larger than FC SIRM, resulting in R LT < 1. Recently, Carter-Stiglitz et al (2006) convincingly argued that, in addition to Kosterov's "geometrical" mechanism, higher coercivity of MD grains after zero field cooling can be caused by the presence of "hard" magnetic 90…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because in MD grains saturation remanence is related to coercivity through the demagnetizing factor (SIRM ∝ H c /N ; e.g., Dunlop andÖzdemir, 1997), ZFC SIRM will be larger than FC SIRM, resulting in R LT < 1. Recently, Carter-Stiglitz et al (2006) convincingly argued that, in addition to Kosterov's "geometrical" mechanism, higher coercivity of MD grains after zero field cooling can be caused by the presence of "hard" magnetic 90…”
Section: Discussionmentioning
confidence: 99%
“…For single-domain (SD) magnetite, the FC SIRM is always greater than the ZFC SIRM (e.g., Moskowitz et al, 1993;Carter-Stigliz et al, 2002). In contrast, for large multidomain (MD) magnetite grains, the FC SIRM has been found to be significantly lower than the ZFC SIRM (e.g., Kosterov, 2001;Brachfeld et al, 2002;Carter-Stiglitz et al, 2006). Such a difference in the R LT ratio reflects different mechanisms governing the SIRM acquisition in single-domain and multidomain magnetite below T V (Kosterov, 2003).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…One sample (TNZ03-08-41) showed clear transition temperature~35 K. If this transition indicates the pyrrhotite, it has remanent magnetization at room temperature and may affect paleointensity experiment. The intensity of FC remanence was larger than that of ZFC remanence, which is a characteristic behavior of SD and fine-grained PSD magnetite (Moscowitz et al 1993;Kosterov 2003;Carter-Stiglitz et al 2006), although the zircon crystals may contain magnetic minerals other than pure magnetite.…”
Section: Low-temperature Magnetometrymentioning
confidence: 99%
“…The FC and ZFC paths for this sample track closely together, except below about 50 K, where the FC curve is higher, and both FC and ZFC warming curves decrease rapidly between 20 and 50 K and continue to decrease above T V . When MD magnetite is the dominant remanence carrier, the ZFC curve is usually higher than the FC curve, at least up to T V (Carter‐Stiglitz et al, ), and most of the remanence is lost in a steep decrease around the Verwey transition. Brachfeld et al () attributed similar FC/ZFC curve behavior to that shown in Figure to the presence of mixed “PSD” (vortex state) and SP grains.…”
Section: Resultsmentioning
confidence: 99%